Penerapan BIM Menggunakan Software Archicad pada Perencanaan Gedung Asrama Putra Pondok Pesantren Baitul Makmur Surabaya - Achmad Rosyid Wahyu Pabelan (Jurnal Vokasi Teknik Sipil, 2024)
The implementation of the Building Information Modeling (BIM) concept is one of the significant innovations in the construction sector. Considering the substantial benefits of using BIM in construction projects and its high adoption rates in developed countries, yet recognizing the disparity in BIM software selection in Indonesia, this research aims to evaluate the outcomes of applying the BIM concept using ArchiCAD software in the building planning process. A case study was conducted on the planning of the Boys' Dormitory Building at the Baitul Makmur Islamic Boarding School in Surabaya, where the building was remodeled using ArchiCAD. This modeling produced outputs that were then analyzed as planning results. The findings indicate that ArchiCAD can apply the 3D BIM concept by automatically generating work volumes. The Budget Plan (RAB) obtained through BIM with ArchiCAD amounts to Rp. 3,743,234,392.57, which is 5.18% lower than the RAB from the planning consultant.